On The Temporal and Spectral Characteristics of Micro-Milling Dynamics - Halfmann, Eric B.; Suh, C. Steve (Journal of Vibration Testing and System Dynamics, 2026)
Due to different chip formation mechanisms, increased tool-radius to feed-rate ratio, and higher spindle speeds, micro-milling is a highly nonlinear process which can produce multiple and broadband frequencies that negatively impact the process. Micro-milling is investigated through the development and analysis of a nonlinear micromilling dynamic model. A lumped mass-spring-damper system is assumed for modeling the dynamic properties of the tool. The force mechanism utilized is a slip-line field model that provides the advantage of being highly dynamic by accounting for the constantly changing effective rake angle and slip-line variables. Accurate prediction of the chip thickness is important in correctly predicting the dynamics of the system since the force mechanism and its variables are a function of the chip thickness. A novel approach for calculating the instantaneous chip thickness which accounts for the tool jumping out of the cut and elastic recovery of the workpiece is presented. The derivation for the effective rake angle is given and the helical angle is accounted for resulting in a three dimensional micro-milling model. The model generates the high frequency force components that are seen in experimental data available in literature. The effect that the helical angle and system stiffness has on the resulting cutting forces is also investigated. It is shown that dynamic instability has the greatest impact on tool performance and improving the dynamic response is a necessity for achieving high speed ultra-stable micro-machining.